Éducation et formation dans les daara : la tarbiyah dans la Murîdiyah - Cheikh Mouhamadou Bamba THIOUNE; Assane DIAKHATE (Revue Hybrides)
Mainly based on the Koran, Islamic education took shape on the day the Revelation began. In Senegal, its favorite places are the daaras, Koranic schools. These base their action on teaching/learning and tarbiyah: educational process enlightened by the light of sharia (Muslim law) and haqîqah (esoteric reality)… How do they deploy the process in the daaras, particularly in the daara tarbiyah which name derives from a Wolof deformation of the Arabic words daaru (house) and al tarbiyah (education)? This article sets out to describe it. Starting from an overview of brotherhoods in Africa and Senegal, it reveals its epistemological and ideological foundations, before indicating its specificity in the Murîdiyah, a Sufi order founded by Cheikh Ahmadou Bamba Mbacké (1853-1927). The field of study is the daara in general, those of Khelcom in particular. The data are collected using the main techniques of qualitative research, following an ethnographic approach. The observation is participatory and armed, the interview is semi-directive. It is also made use of the documentary collection and the analysis of discourse. The results indicate that the tarbiyah aims at spiritual improvement, purification of the soul, and education to values… Its processes are Takhliyah (stripping the individual of all his faults) and Tahliyah (embellishment of the ‘be). In the Murîdiyah, its basis is the spiritual motivation (al himma) and the principle, the fact of working, exclusively, for the Face of God (al khidma). Within the daara the three dimensions of the individual are taken into account: mind, body and heart, through instruction, education, and elevation. The tools of tarbiyah are the Koran, books of religious sciences, qaçaids (odes), litanies, sermons and tomb (explanatory diagrams), concomitantly with domestic and rural work.